2022
DOI: 10.1080/07853890.2022.2131328
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in the incidence and survival of stage I liver cancer: a surveillance, epidemiology, and end results analysis

Abstract: Background Improvements in screening and imaging technologies and treatment of liver disease have influenced the trend in diagnosis for stage I liver cancer. In this article, recent trends in age, incidence, tumour size, and survival of different stages of liver cancer are analysed. Methods Surveillance, Epidemiology, and end results data from the National Cancer Institute were used to analyse trends in age-adjusted incidence rate, mean tumour size at diagnosis, age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“… 28 Previous data shows a significant increase in the incidence of early-stage HCC between 2004 and 2015. 29 Our study expands upon existing literature by revealing a decline in HCC incidence among younger men but not women, which was mostly attributable to early-stage tumors. Previous literature indicated that younger women are more inclined to undergo regular HCC surveillance, which may lead to a higher percentage of early-stage tumors being detected.…”
Section: Discussionsupporting
confidence: 78%
“… 28 Previous data shows a significant increase in the incidence of early-stage HCC between 2004 and 2015. 29 Our study expands upon existing literature by revealing a decline in HCC incidence among younger men but not women, which was mostly attributable to early-stage tumors. Previous literature indicated that younger women are more inclined to undergo regular HCC surveillance, which may lead to a higher percentage of early-stage tumors being detected.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have shown that the overall 5-year survival rate of HCC is decreasing. Although the survival rate of early-stage HCC is still high, the prognosis of advanced HCC is not optimistic [ 16 ]. And when it comes to prognosis, the major obstacle to improving the prognosis of patients with HCC is that metastasis and recurrence occur in 60 to 80% of patients [ 17 ].…”
Section: Biological Classification and Current Status Of Liver Cancermentioning
confidence: 99%